2015
DOI: 10.1016/j.biopsych.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA-Directed Epigenetic Regulation of Gene Expression Is Associated With Anxiety-like Behavior in Mice

Abstract: Background RNA-directed regulation of epigenetic processes has recently emerged as an important feature of mammalian differentiation and development. Perturbation of this regulatory system in the brain may contribute to the development of neuropsychiatric disorders. Methods RNA sequencing (RNA-seq) was used to identify changes in the experience-dependent expression of long non-coding RNAs (lncRNAs) within the medial prefrontal cortex (mPFC) of adult mice. Transcripts were validated by real-time quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(130 citation statements)
references
References 121 publications
1
127
1
1
Order By: Relevance
“…A recent study demonstrated that antisense-oligo-mediated gene knockdown of Gomafu in the medial prefrontal cortex in the mouse brain affected the anxiety-related behaviors of mice in the fear-conditioning test and open field test16. However, we could not detect any differences between the WT and KO mice in the fear-conditioning test (Figure S6), which was consistent with the observation that the KO mice did not exhibit any behavioral changes that were related to anxiety in the open field test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that antisense-oligo-mediated gene knockdown of Gomafu in the medial prefrontal cortex in the mouse brain affected the anxiety-related behaviors of mice in the fear-conditioning test and open field test16. However, we could not detect any differences between the WT and KO mice in the fear-conditioning test (Figure S6), which was consistent with the observation that the KO mice did not exhibit any behavioral changes that were related to anxiety in the open field test.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Gomafu is also downregulated in the brains of patients with schizophrenia12. Recent studies associate Gomafu with stress and anxiety and suggest that Gomafu can affect anxiety behaviors in mice by affecting the expression of the schizophrenia-related gene β-crystallin (Crybb1) through binding to PRC116. Gomafu is also proposed to regulate transcription by acting as a competing RNA for miRNA to regulate genes associated with microvascular dysfunction17.…”
mentioning
confidence: 99%
“…Moreover, GOMAFU was recently reported to play a role in mediating anxiety-like behavior through interacting with a key member of the polycomb repressive complex 1 (BMI1), and thus modulated the expression of the schizophrenia-related gene beta crystallin (Crybb1). Crybb1 is also an important factor in mediating fear-induced anxiety-like behavior (Spadaro et al, 2015). A non-protein-coding RNA, MALAT-1 (also known as NEAT2) is upregulated in the human cerebellum, hippocampus and brain stem induced by alcohol, suggesting an important novel mechanism for alcohol actions in the CNS (Kryger et al, 2012).…”
Section: Lncrnas Related To Synaptic Plasticity Potentially Associatementioning
confidence: 99%
“…A more localized, tissue-specific interference of lncRNAs using RNAi can also have phenotypic consequences. shRNA-mediated downregulation of Miat (also known as Gomafu) in the medial prefrontal cortex of the brain promotes anxiety-like behaviors (75), while local siRNA-mediated downregulation of Munc, which is specifically expressed in skeletal muscle, impairs myogenesis (76). Additionally, the use of an shRNA to revert the upregulation of Arid2-IR in the mouse kidney following renal inflammation also reverts the biochemical signatures of this condition (77).…”
Section: Animal Models and Lncrna Functionmentioning
confidence: 99%